A New Model For Work Stress Patterns - Barhem, Belal; Md Sidin, Samsinar; Abdullah, Iskandar; Alsagoff, Syed Kadir (Asian Academy of Management (AAM), 2004)
This study tests a new work stress model by evaluating the major work stress sources and work stress coping strategies experienced by the Malaysian and Jordanian Customs Department employees. It further ranks the sources and coping strategies of work stress, and evaluates the relationships between stress patterns. The sample consists of 216 Malaysian Customs employees and 248 Jordanian Customs officers, from which correlation, means, path analysis and frequencies were computed. The major findings of the study show that Malaysian and Jordanian Customs employees identified role ambiguity as the main source of work stress while self-knowledge was the major coping strategy they used to overcome work stress. The relationship between sources of work stress and coping strategies is strong in the two cases while the relationship with personal differences is weak.